Assessment report on potential GIFT receiving facilities in Côte d’Ivoire - Attia, Sameh; Mengistu, Samuel (WorldFish, 2025)
This report presents the results of an assessment of a quarantine facility and three hatcheries in Côte d’Ivoire. The objective of the assessment was to check the readiness of the facility and the hatcheries to receive the Genetically Improved Farmed Tilapia (GIFT) strain of tilapia from WorldFish Malaysia. Two WorldFish scientists traveled to Côte d’Ivoire, where they had an initial consultative meeting with key government stakeholders and interviewed managers at the quarantine facility and the hatcheries. They conducted a practical assessment of the facilities during comprehensive site visits on December 18–23, 2024. The assessment focused on existing infrastructure, biosecurity measures and the technical capabilities necessary to successfully quarantine the soon-to-be-imported GIFT fry and the subsequent nursery, grow-out and multiplication phases required to establish a tilapia breeding program in the country. The quarantine facility and the three hatcheries did meet the minimum requirements. However, they still require a number of important improvements based on the results of the assessment, and the staff at all of the facilities would benefit from additional training and technical support.